Distance Students as Virtual Migrants: A Case Study from Atlantic Canada - Greene, Melanie Jennifer; Kirby, Dale (Alberta Journal of Educational Research, 2014)
Distance learners are typically excluded from discussions of student mobility. This paper explores distance student choices and experiences, drawing on a study that included students who enrolled in distance education courses at a university outside of their home province. Findings from this study suggest that program and course considerations such as quality, accessibility, and reputation were of primary importance to distance learners. Program cost was also found to be influential in students’ decision-making. Overall, this study adds to the current literature on distance student enrolment choices, experiences, and expectations. It makes a significant contribution in identifying factors that may result in students’ enrolment in distance education outside of their home region, and that should be considered in university recruitment initiatives. Typiquement, les apprenants à distance sont exclus des discussions sur la mobilité des étudiants. Cet article explore les choix et les expériences des étudiants à distance en puisant dans une étude qui a inclus des étudiants inscrits à des cours à distance offerts par une université située dans une province autre que la leur. Les résultats portent à croire que, par rapport aux programmes et aux cours, les apprenants à distance tiennent surtout compte de la qualité, l’accessibilité et la réputation. Le cout des programmes entre également en ligne de compte dans le choix de cours par les apprenants. Globalement, cette étude ajoute à la documentation existante sur les choix de cours, les expériences et les attentes des étudiants à distance. Elle contribue de manière importante à l’identification des facteurs qui pourraient entrainer l’inscription par des étudiants à des cours ailleurs que dans leur région de résidence et dont devraient tenir compte les initiatives de recrutement à l’université.